Strategy to Increase Employee Loyalty of Mikro Regular Ulamm Account Officers PT. Permodalan Nasional Madani in the Tegal Branch Working Area - Ramadhan Firmansyah; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a descriptive qualitative research, in which the author must conduct observations and interviews as well as documentation about the performance of Account Officers at PT PNM Tegal Branch. Loyalty and low Account Officer performance can result in decreased bank profits so that a strategy is needed to increase the loyalty of PT Permodalan Nasional Madani (PT.PNM) Account Officers. The strategies used include SWOT analysis, an analysis that has strategic planning techniques and methods to determine and evaluate the strengths, weaknesses, opportunities, and threats of a company. The purpose of this SWOT analysis is to increase the loyalty of ULaMM Account Officer performance